Tunisia: The Need for a New Development Model - Klai, Hmida (Journal of Applied Business and Economics, 2022)
The Tunisian revolution took everyone by surprise. What were the immediate causes of this historic event? What are the economic and financial challenges facing the country? How can they be addressed? The Tunisian revolution has proven the failure of the development model that has been in force since the seventies. The country is, today, facing major economic and social challenges, mainly recession, unemployment, regional disparity, a growing budget and current account deficit, a high inflation rate in addition to a heavy external public debt. The low level of national savings makes external financing the greatest challenge in the short and medium term. What development strategy should be followed? The objective of this article is to search for an appropriate development model that is capable of achieving the country’s economic and social objectives; the determination of adequate and coherent policies for its operation; and finally to provide the decision makers with practical recommendations to be implemented.